PENGARUH RELEVANSI NILAI INFORMASI OTHER COMPREHENSIVE INCOME DAN NET INCOME TERHADAP RETURN SAHAM - Titik Aryati; Natasya Nadia Wibowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
This research has a purpose to analyze the influence value relevance of information Other Comprehensive Income and Net Income in explaining Stock Return by using control variables, namely Firm Size, Growth, Debt to Total Assets, and Return on Assets. The sample used in this research are manufacturing companies which is listed in Indonesian Stock Exchange from 2011 to 2015. Obtained by 53 manufacturing companies the research sample. Data used in this research are secondary data obtained from the form of the annual audited financial statements derived from the Indonesia Stock Exchange (IDX) the period of 2011-2015 and the Indonesian Capital Market Directory (ICMD) in the period 2011-2015. The statistic method used to test on the research hypothesis is panel data analysis. The research results found that variables of the research model which are Other Comprehensive Income has a negative and significant effect on stock return, whereas Net Income has a positive and significant effect on stock return.